HIV disease skin and mucous membrane manifestations - Johnson, Richard Allen, 1940-; Dover, Jeffrey S.; Marion & Roberta Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education (Evanston, IL : American Academy of Dermatology, 1991)
Covers neoplasms, viral infections, bacterial infections and miscellaneous dermatoses in HIV disease
Keywords: HIV infections; Acquired immunodeficiency syndrome; Skin Manifestations